Child Abuse In Dave Pelzer's Trilogy A Child Called It (1993), The Lost Boy (1995), And A Man Named Dave (1999) - Hidayati, Fajria Nurul; , Dr. Phil Dewi Candraningrum, M.Ed; , Drs. M. Thoyibi, M. S. (2015)
This research paper analyzes child abuse that is reflected in Dave Pelzer's trilogy A Child Called it, The Lost Boy, and A Man Named Dave. The objectives of the research are to identify the context of the production of the trilogy, to analyze the influence of environment on the personality development of the author, and to review the reflection and criticism of the author towards child abuse. The research paper belongs to qualitative research. The sources of data come from both primary data source and secondary data sources. The method to analyze the data is descriptive analysis. The researcher finds the main finding in which there is relationship between the trilogy and the American society at the end of the twentieth century. It can be broken into three: First, there is a close relationship between the productions of trilogy and the American society at the end of twentieth century. Second, the environments where the author lived influenced his personality development and behavior. Third, through the trilogy, the author conveys his critique to parents, society and the victims.